The parasite complex of the citrus psylla, trioza erytreae (Del Guercio) (Homoptera) - McDaniel, J. R. (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1971)
1. Fifteen parasite species comprising the T. erytreae complex in Salisbury are listed. 2. Detailed, illustrated accounts are given of the biology of two primary parasites, Tetrastichus Pradiatus Waterston and Psyllaephagus pulvinatus (Waterston ), and their main hyperparasite, Aphidencyrtus cassatus Annecke. 3. The biology of the remaining twelve less important hyperparasites is briefly described and illustrated. 4. Keys are given to the adults, pupae and pupal remains of the parasites. 5 . The population fluctuations of T. erytreae and its parasites, as determined from field studies in the Salisbury area, are reported . 6. The interrelationships between T. erytreae and its parasites are summarised and discussed. Summary, p. 89.
Keywords: Psylla -- Regulation; Citrus; Biological control systems; Parasites